Is there any association between manganese level and schizophrenia?- a descriptive review - Juchnowicz, Dariusz; Karakuła, Kaja Hanna; Sitarz, Elżbieta; Forma, Alicja; Padała, Olga; Ryczkowski, Aleksander Janusz (Current Problems of Psychiatry, 2020)
Introduction. Manganese has a role in the membrane transport systems, synthesis of protein, vitamin C, and vitamins B, catalysis of hematopoiesis, regulation of the endocrine, immune system, blood sugar, reproduction, digestion, and blood coagulation. Furthermore, the level of manganese concentrations in human body appears to affect the occurrence of schizophrenia. The aim of this study was to search for relationships between the manganese level and the onset of schizophrenia. Material and methods. A descriptive review was performed based on a literature search on Medline and Google scholar from 2003 to 2020, using keywords: schizophrenia, manganese, Mn. The included studies were meta-analyses, case-control studies, and cohort studies that examined differences in manganese concentrations in patients with schizophrenia and healthy controls. Result. Eight studies were selected for the review, with one reporting elevated levels of manganese, two showing no significant differences, and the rest including two meta-analyses stating lower manganese concentrations in patients with schizophrenia in comparison with controls. Conclusion. In most of the researched studies, manganese concentrations in patients with schizophrenia were lower than in control groups, but not all of them reached the same conclusions. The relationship between manganese levels and schizophrenia must be further investigated.